Mountain climbing guide application for beginners - Margaretha Sinurat, Monica Florent Natalie; Wulandari , Sri (Jurnal Mantik, 2024)
Mountaineering has become a popular activity in Indonesia, but many beginner climbers are still unprepared, making them vulnerable to accidents. This study aims to design and develop a web- and mobile-based mountaineering guide application for beginners that provides comprehensive information related to physical and mental preparation, as well as survival techniques. This application is equipped with a guide to climbing rules, necessary equipment, first aid procedures, and survival based on Mapala standards. In addition, this application offers recommendations for safe and suitable climbing routes for beginners on various mountains in Indonesia. The research methods used include data collection, business rule analysis, and implementation of easy-to-understand user interface design. The result of this research is an application that helps climbers prepare for their trips in a safer and more structured manner. User trials show that the application greatly benefits beginner climbers, with a high success rate in increasing their readiness and knowledge. Recommendations for improvements for further development are also presented to improve the quality of the application in the future